Technology ventures : from idea to enterprise - Byers, Thomas [ (Thomas H.)]; Dorf, Richard C.; Nelson, Andrew J. (McGraw Hill, 2011)
Suitable for business, engineering, and science students and professionals, this title analyzes the opportunities to build enterprises. It offers a perspective on 'technology', including clean tech, information technology and the life sciences. It covers university technology commercialization, open source innovation, and social entrepreneurship